Faktor-Faktor yang Mempengaruhi Anemia - Permata, Intan Indra; Achyar, Khamidah; Kusuma, Inggar Ratna (Jurnal Riset Kesehatan Masyarakat, 2023)
Anemia is a condition in which the oxygen-carrying capacity of the blood is insufficient. Our previous study found that in Soreang Regency, which is a rural area, the prevalence of anemia among female students was 14.3%. The government is running an iron supplementation program to treat IDB in young people. This research uses a literature review. A literature search through journal publications in PubMed and also Google Scholar using the keywords "risk factor" and "anemia" obtained from PubMed a total of 7 articles included in inclusion and 4 Google Scholar articles included in this research. This study found a longitudinal relationship between total anemia iron intake/day and IDA in adolescents. Several cross-sectional studies have shown that iron intake is significantly associated with anemia. The nutritional status of adolescents can be improved by consuming nutritional complementary foods. Nutritional status is positively correlated with hemoglobin concentration, ie. H. The worse a person's nutritional status, the lower the Hb level. Teenage girls are more susceptible to anemia because they tend to look thin and want to limit their nutritional intake, and girls menstruate every month. Iron loss is estimated to be ± 1.3 mg/day, so iron requirements are higher than for men.